Exulowie wszystkich czasów, czyli Owidiusz i inni - Milewska-Waźbińska, Barbara (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The aim of this paper is to examine how 20th century draws inspiration from Ovid’s exile and his works. The paper examines how Jacek Kaczmarski offers a poet “a response” to Ovidian exile.
The Exuls of All the Times or Ovid and the Others
In the title of this paper there is a quotation from Zbigniew Herbert’s famous poem: Why classics? The article refers to the fates of “poets of exile”. It is pointed out that the fate of Ovid is a recurring feature of the exile poetry. The paper examines how Jacek Kaczmarski (1957-2004), who was not allowed to return to Poland until 1990, offers in his song The Old Age of Ovid a “response” to Ovidian exile from Rome.
Keywords: poetry of exile; Ovid; Jacek Kaczmarski